2004
DOI: 10.5194/bg-1-123-2004
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope anomaly in the major plant C<sub>1</sub> pool and its global biogeochemical implications

Abstract: Abstract. We report that the most abundant C 1 units of terrestrial plants, the methoxyl groups of pectin and lignin, have a unique carbon isotope signature exceptionally depleted in 13 C. Plant-derived C 1 volatile organic compounds (VOCs) are also anomalously depleted in 13 C compared with C n+1 VOCs. The results confirm that the plant methoxyl pool is the predominant source of biospheric C 1 compounds of plant origin such as methanol, chloromethane and bromomethane. Furthermore this pool, comprising ca 2.5%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
131
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 36 publications
(40 reference statements)
16
131
3
Order By: Relevance
“…An exceptional case amongst the NMHCs is CH 3 OH which emitted significantly depleted 13 C with respect to the material burned, as shown by Yamada et al (2009). They attribute changes to the emission δ 13 C signature to the variations in the fraction of the precursor material (pectin vs. lignin methoxy pools; see also Keppler et al, 2004) and kinetic effects in loss processes. The overall depletion of CH 3 OH with respect to the plant material is found to linearly correlate with the fire-modified combustion efficiency (MCE = CO 2 /( CO + CO 2 ), denotes trace gas concentration enhancement due to emission).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…An exceptional case amongst the NMHCs is CH 3 OH which emitted significantly depleted 13 C with respect to the material burned, as shown by Yamada et al (2009). They attribute changes to the emission δ 13 C signature to the variations in the fraction of the precursor material (pectin vs. lignin methoxy pools; see also Keppler et al, 2004) and kinetic effects in loss processes. The overall depletion of CH 3 OH with respect to the plant material is found to linearly correlate with the fire-modified combustion efficiency (MCE = CO 2 /( CO + CO 2 ), denotes trace gas concentration enhancement due to emission).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…For the fractionation escorting isoprene emission, the lower limit of 4 ‰ depletion relative to the bulk leaf composition from Affek and Yakir (2003) is taken. In the case of methanol, significantly larger depletions (about 40 ‰) were discovered by Keppler et al (2004) and linked to highly depleted pectin and lignin methoxyl pools which plants likely use to produce CH 3 OH. A later work by Yamada et al (2010) confirmed similar fractionations for a different set of C 3 plants species.…”
Section: Plant Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from biotic production of living plants, an abiotic reaction pathway has been described for CH3Br following a nucleophilic substitution reaction (SN2) (Hamilton et al, 2003;Keppler et al, 2004). The methoxy groups of pectin and lignin, both abundant cell-stabilizing macromolecules, react with halide ions dissolved in the tissue water of the plants (Khan et al, 2001) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hence stable isotope techniques are starting to be explored to improve the source apportionment of methyl halides. Carbon-13 analysis on atmospheric samples was first shown for CH3Cl by Rudolph et al (1997) and since then it was applied in various studies to characterize source (Thompson et al, 2002;Keppler et al, 2004;Saito and Yokouchi, 2008) and sink signatures (Gola et al, 2005;Sellevag et al, 2006). A first δ 13 C isotope based budget estimate was accomplished by Keppler et al (2005).…”
Section: Introductionmentioning
confidence: 99%